SOSIALISASI PEMBERDAYAAN PEREMPUAN DAERAH PESISIR DALAM RANGKA PENINGKATAN KETAHANAN PANGAN DI MUSIM PANDEMI, KECAMATAN BATANG, KABUPATEN BATANG, JAWA TENGAH - Kurniasih, Pritha (Pengabdian Masyarakat, 2023)
Socialization activities for Empowerment of Coastal Women to increase food security during the pandemic season, Batang District, Batang Regency, Central Java. With the hope that implementing this activity can benefit fishermen's wives around the Batang coast. On future occasions, it hopes that there will be more community service activities, both independent and integrated, while still involving resource persons, especially lecturers at the Politeknik Ilmu Pelayaran Semarang.